Pengaruh Media Tanam Hidroponik terhadap Pertumbuhan Bayam (Amaranthus sp.) dan Selada (Lactuca sativa) - Renna Eliana Warjoto; Tati Barus; Joshua Mulyawan (Jurnal Penelitian Pertanian Terapan, 2020)
As the human population rises, the demand for high nutritional foods, such as vegetables, also increases. However, agricultural land, especially in urban areas, is narrowing. Hydroponics can be one of the solutions to answer this problem. In addition to complete nutrition, hydroponic plants also require appropriate media for root attachment, water absorption, and aeration. Unfortunately, no studies have compared the growth of hydroponic plants using rockwool and sponge as affordable growing media. Therefore, this study aimed to determine the effect of local rockwool, imported rockwool, and sponge as growing media on the growth of spinach  (Amaranthus sp.) and lettuce  (Lactuca sativa) using Deep Flow Technique (DFT). This study used a Completely Randomized Design with three treatment groups, i.e., three different growing media, for spinach and lettuce. At the harvest period, the number of leaves on each plant was counted, the crown fresh-weight was balanced, and the chlorophyll content was determined. Plant height was also measured for spinach. The results showed that the three types of growing media had no significant effect on the number of leaves, plant height, crown fresh-weight, and chlorophyll content of spinach. However, the number of leaves  (25.25 ± 1.38) and the crown fresh-weight  (141.27 ±16.49 g) of lettuce grown on the local rockwool media were significantly higher than the number of leaves (17.00 ± 0.77) and the crown fresh-weight (81.48 ± 9.50 g) of lettuce planted on the sponge media. Other hydroponic growing media’s influences can be investigated for further research, with additional growth parameters such as crown dry- weight, root fresh- and dryweight, as well as the determination of plant phytochemical contents. Moreover, the correlation between nutritional formulations and the type of growing media can be further examined to obtain the most optimum spinach and lettuce growth.